Analysis of reach‐scale elevation distribution in braided rivers: Definition of a new morphologic indicator and estimation of mean quantities. Issue 8 (10th August 2016) - Redolfi, M.; Tubino, M.; Bertoldi, W.; Brasington, J.
Abstract: Understanding the role of external controls on the morphology of braided rivers is currently limited by the dearth of robust metrics to quantify and distinguish the diversity of channel form. Most existing measures are strongly dependent on river stage and unable to account for the three‐dimensional complexity that is apparent in digital terrain models of braided rivers. In this paper, we introduce a simple, stage‐independent morphological indicator that enables the analysis of reach‐scale regime morphology as a function of slope, discharge, sediment size, and degree of confinement. The index is derived from the bed elevation frequency distribution and characterizes a statistical width‐depth curve averaged longitudinally over multiple channel widths. In this way, we define a "synthetic channel" described by a simple parameter that embeds information about the river morphological complexity. Under the assumption of uniform flow, this approach can be extended to provide estimates of the reach‐averaged shear stress distribution, bed load flux, and at‐a‐station‐variability of wetted width. We test this approach using data from a wide range of labile channels including 58 flume experiments and three gravel bed braided rivers. Results demonstrate a strong relationship between the unit discharge and the shape of the elevation distribution, which varies between a U shape for typical single‐thread confined channels and a Y shape for multithread reaches. Finally, we discuss the use of the metric as a diagnostic index of river condition that may be used to support inferences about the river morphological trajectory. Key Points: Reach‐averaged braided river morphology is explored using flume and field data, and numerical models We introduce a reach‐scale index based on bed geometry and we test how it changes with key controls This enables to estimate bed shear stress and at‐a‐station variability of bed load flux and width